Essential Role for FtsL in Activation of Septal Peptidoglycan Synthesis - Kyung-Tae Park (American Society for Microbiology, 2020)
ABSTRACT Spatiotemporal regulation of septal peptidoglycan (PG) synthesis is achieved by coupling assembly and activation of the synthetic enzymes (FtsWI) to the Z ring, a cytoskeletal element that is required for division in most bacteria. In Escherichia coli, the recruitment of the FtsWI complex is dependent upon the cytoplasmic domain of FtsL, a component of the conserved FtsQLB complex. Once assembled, FtsWI is activated by the arrival of FtsN, which acts through FtsQLB and FtsA, which are also essential for their recruitment. However, the mechanism of activation of FtsWI by FtsN is not clear. Here, we identify a region of FtsL that plays a key role in the activation of FtsWI which we designate AWI (activation of FtsWI) and present evidence that FtsL acts through FtsI. Our results suggest that FtsN switches FtsQLB from a recruitment complex to an activator with FtsL interacting with FtsI to activate FtsW. Since FtsQLB and FtsWI are widely conserved in bacteria, this mechanism is likely to be also widely conserved. IMPORTANCE A critical step in bacterial cytokinesis is the activation of septal peptidoglycan synthesis at the Z ring. Although FtsN is the trigger and acts through FtsQLB and FtsA to activate FtsWI the mechanism is unclear. Here, we find an essential role for FtsL in activating septal peptidoglycan (PG) synthesis and find that it acts on FtsI. Our results suggest a model where FtsWI is recruited in an inactive form by FtsQLB, and upon the arrival of FtsN, FtsQLB undergoes a conformational change so that a region of FtsL, which we designate the AWI domain, becomes available to interact with FtsI and activate the FtsWI complex. This mechanism for activation of the divisome has similarities to the activation of the elongasome and is likely to be widely conserved in bacteria.